Application of the Cooperative Integrated Learning Model Reading and Composition to Improve Chemistry Learning Outcomes - Fatimah, Tati (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: The aim of this research is to improve the chemistry learning outcomes of class X students at Public High School 5 Bandar Lampung through the implementation of the Cooperative Integrated Reading and Composition (CIRC) cooperative learning model. Methodology: The subjects in this research were 18 class X Public High School 5 Bandar Lampung students. Meanwhile, the object of this research is the application of the Cooperative type cooperative learning model Integrated Reading and Composition (CIRC) to improve chemistry learning outcomes for class X Public High School 5 Bandar Lampung. Main Findings: Based on research results, the application of cooperative learning strategies of the Cooperative Integrated Reading and type Composition (CIRC) in the learning process in class X Public High School 5 Bandar Lampung improves student learning outcomes. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of implementing the cooperative integrated reading and composition (CIRC) type cooperative learning model to improve chemistry learning outcomes. In addition, this research also contributes to the educational literature by presenting empirical data regarding the effectiveness of CIRC in improving understanding and retention of chemistry material.